Implementation of the Picture and Picture Learning Model to Improve Pancasila and Citizenship Education Learning Outcomes for Elementary School Students - Dewi Anzelina; Eliyawati Eliyawati; Nashran Azizan; Maulana Arafat Lubis (PIONIR: JURNAL PENDIDIKAN, 2023)
The learning model is a design pattern that aims to ensure that learning objectives are achieved effectively and efficiently so that it impacts student learning outcomes, which are expected to get excellent grades and gain something meaningful from the learning experience of elementary school students. The research aims to improve learning outcomes in Pancasila and Citizenship Education subjects in the aspects of spiritual attitudes, social attitudes, knowledge, and skills of students through the application of the picture-and-picture learning model on the subject matter of obligations and rights and responsibilities as citizens. The research subjects were 28 class III-B students at SDN 200220 Padangsidimpuan. This research uses the Kurt Lewin model of classroom action research methods. Data collection uses tests and observations. Data were analyzed descriptively using quantitative and qualitative approaches. The research results prove that students experienced an increase in their learning outcomes. Starting from cycle I, meeting I, only 12 students completed it, cycle I meeting II increased to 17 students who completed it, cycle II meeting I increased to 20 students completing it, and cycle II meeting II increased again to 25 students completed with an average score of 89.2 or 89.28%.